Growth and Survival Rate of the Snakehead (Channa striata) Larvae Fed with Different Natural Feeds - Siti Mahardika; Mustahal Mustahal; Forcep Rio Indaryanto; Adang Saputra (Jurnal Perikanan dan Kelautan, 2017)
Snakehead is a kind of fresh water fish that still taken from the nature, which is the yieldof it fishing are unreliable. Therefore, the aquaculture technique is needed. Criticalphase of snakehead aquaculture is choosing suitable feed for larvae. Based on this problem, information about first feed suitable for larvae is very important.The aim of the research is to know about growth and survival rate of snakehead larvae with differentfeed. The research was done in 21 days at the Center for Research and Development ofFreshwater Aquaculture Bogor. Larvae with first weight 0.4±0.07 mg and length 4.56±0.53 mm were used. Fish were feed three times daily in ad satiation. Experimentaldesign used was completely randomized design four treatment with three replications,namely A (egg yolk chicken), B (Moina sp,), C (Artemia sp.) and D (silk worm).Parameters measured were the absolute length growth, the growth of absolute weight,specific growth rate, survival rate and feed efficiency. Water quality parameters weretemperature, pH, DO and conductivity. The result showed that the used of silk worm asfirst feed for larvae indicated the best performences. The growth of the absolute length of13.34±1.30 mm, absolute weight of 54.52±2.93mg, specific growth rate 23.85±0.21%,survival rate 97.67±2.36% and feed efficiency 82.69±7.79%.  Keywords : feed, growth, larvae, silk worm, snakehead, survival rate.